APPLICATION OF THE CERTAINTY FACTOR METHOD FOR DIAGNOSE PALM OIL DISEASE WEB-BASED - isna isnaini; Iqbal Kamil Iqbal; Muhammad Ihsan Ihsan (Informatika, Universitas Jenderal Soedirman, 2022)
Expert systems can serve as consultants advising users as well as expert assistants. One way to overcome and help detect disease in oil palm is to create an expert system as a media for consultation on oil palm plantations so as to minimize the occurrence of disease attacks that result in crop failure. This research uses qualitative research methods and is included in descriptive research. The data analysis method used in this research is the Cetainty Factor method and the search method used is forward data searching to find conclusions. Data collection techniques through interviews and literature study. This research uses PHP programming language with MySQL database. With the application of an expert system with the certainty factor method, it is expected and stored as a knowledge database in an expert system, it can help farmers to identify pests/diseases of oil palm quickly so that treatment does not last long.